PENGARUH PENGGUNAAN MEDIA FLASHCARD TERHADAP HASIL BELAJAR IPA SISWA KELAS IV SDN KOMPLEKS IKIP - Eka Mey Wulandari Astuti; Hilmi Hambali; A.Muafiah Nur (STKIP Subang, 2024)
The main problem in this research is how to use flashcard media to improve science learning outcomes for class IV students at SDN IKIP Complex. This research aims to find out whether flashcard media has an effect on science learning outcomes at SDN IKIP Complex and how the use of flashcard media affects science learning outcomes at SDN IKIP Complex. This research uses a pre-experimental design research type with a Nonquivalent Control Group Design. The subjects of this research were 54 grade IV students at SD N IKIP Complex. This research was carried out 4 times face to face. Data collection techniques were carried out using learning outcomes tests and observation data. The collected data was analyzed quantitatively using descriptive statistics and inferential statistics. The results of inferential statistical research using the normality test and homogeneity test of student learning outcomes taught using flashcard media, and for the significant value obtained in the experimental class 0.200 and in the posttest 0.132, the significant value obtained was greater than 0.05 (α > 0.05) so that the data was normally distributed. The homogeneity test obtained sig 0.303, the significant value is greater than 0.05, so the variance between the pretest and posttest classes is the same (homogeneous). Based on the results of this research, it can be concluded that there is an influence on the science learning outcomes of Ikip Complex Elementary School students using flashcard media.